2004
DOI: 10.1103/physrevb.70.165421
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of H intercalation in rutileTiO2

Abstract: The geometry of hydrogen intercalation sites in rutile TiO 2 has been studied using first principles calculations. A new intercalation site is predicted which is consistent with all current experimental data. The apparent contradiction between spectroscopic, diffraction and magnetic resonance data are resolved by taking into account the strong local distortions of the structure induced by localization of donated charge. In particular the predicted OH vibrational frequency is in excellent agreement with that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 24 publications
(33 reference statements)
4
24
0
Order By: Relevance
“…A few accounts of hydrogen incorporation into a rutile TiO 2 lattice have been given. [27][28][29] It remains to explain why the H-atom coverage cannot exceed a critical value and a perfect (1 1) adlayer cannot be obtained, as in the case of H on other oxide surfaces (e.g. ZnOA C H T U N G T R E N N U N G (101 0) [7] ).…”
Section: Resultsmentioning
confidence: 98%
“…A few accounts of hydrogen incorporation into a rutile TiO 2 lattice have been given. [27][28][29] It remains to explain why the H-atom coverage cannot exceed a critical value and a perfect (1 1) adlayer cannot be obtained, as in the case of H on other oxide surfaces (e.g. ZnOA C H T U N G T R E N N U N G (101 0) [7] ).…”
Section: Resultsmentioning
confidence: 98%
“…Several studies have reported a proton-induced shallow level E P below the TiO 2 conduction band. 24,25 The residence time (t) of the electron on a trap site is calculated from the thermionic emission expression,…”
mentioning
confidence: 99%
“…In the rutile structure there are empty channels parallel to the c axis that are bounded by oxygens; the muon (hydrogen) sites are located inside these channels [28]. At these low temperatures, the muon cannot escape from the channel due to a relatively large energy barrier.…”
mentioning
confidence: 99%